Versatility of the Reverse Sural Fasciocutenous Flap for Coverage of Distal Leg, Ankle and Foot - Khaled, Mohammed Shahabuddin; Islam, Mohammad Mazaherul; Gupta, Sammya Das; Dewanjee, Avijit; Palit, Liton Kumar (Journal of Chittagong Medical College Teachers’ Association, 2023)
Background: Coverage at distal leg and foot is always challenging for plastic surgeon as it is less vascular and having minimum muscular tissue. Reverse sural fasciocutenous flap is good and reliable alternative at this territory with same important as free flap. Aim of the study to observe and report our experience with versatile use of Reverse Sural Fasciocutaneous Flap (RSFF) at different position of distal leg, ankle and foot to see functional and aesthetic outcome. Materials and methods: This is a prospective obervational study. Our article contains 20 reverse sural flap coverage at distal leg, ankle and foot from 2019 to 2022, in which we described patient’s demography, surgical anatomy, operative technique, flap dimension, complication and follow up from 6 months for 2 years. We kept vascular pedicle with minimum 2 cm skin tag to relieve venous congestion of flap. Results: All flap cover the defect of traumatic, neoplastic, chronic ulcer, burn and osteomyelitis with good functional and aesthetic outcome. Average flap dimension is 8.95x6.15cm and average wound dimension is 7.95x5.15 cm. only three flap have moderate venous congestion with two show marginal necrosis and one, damaged with skin necrosis in which later on, need skin graft. Conclusion: RSFF show excellent arc of rotation around the ankle make it versatile and confident option and also equivalent to microvascular free flap in this territory. Flap cover ensure early recovery and almost regain normal walk and foot movement. JCMCTA 2023 ; 34 (1) : 132-137